CONCEPT OF AIR TRAFFIC FLOW AND CAPACITY MANAGEMENT IN EUROPEAN REGION - Kharchenko, Volodymyr; Chynchenko, Yuriy (Proceedings of National Aviation University, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> The article deals with the analysis of the researches conducted in field of the air traffic flow and capacity management by Eurocontrol. Traffic flows statistics, air traffic flow and capacity management phases and Enhanced traffic flow management system have been reviewed. Principles of concept implementation and impact on air traffic flow and capacity management have been analysed and general recommendations applicable for Ukrainian aeronautical system have been proposed. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Обычная таблица"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] -->